Stunting prevention counseling and supplementary feeding in Margaasih - Djakwan Vici Mulyadi; Tita Nurjanah; Awalia Latifa Mayda Ikrimah; Dimas Hot Asi Pasiribu (Universitas Pendidikan Indonesia, 2024)
The Supplementary Feeding Program (PMT) is intended to provide additional nutrition to children in need and who are growing. To prevent stunting, this Supplementary Feeding is not only given to children but also to pregnant women. The Supplementary Feeding Program must be adjusted to local conditions, especially local food conditions. The ultimate goal of this program is to ensure that children get the right nutrition so that they grow optimally and reduce the risk of stunting and other nutritional problems. We design activities in the form of counseling and making additional food. Counseling is carried out directly with a lecture method on preventing stunting, which begins with a pre-test, presentation of material, and post-test. The counseling material consists of two main materials, namely breast milk and complementary foods intended to prevent stunting. PMT can be distributed in the form of rice and fish nuggets at the end of the presentation session, which can be practiced at home by pregnant women and mothers of toddlers. Abstrak Program Pemberian Makanan Tambahan (PMT) ditujukan untuk memberikan tambahan nutrisi pada anak-anak yang membutuhkan dan sedang dalam masa pertumbuhan. Dalam rangka pencegahan stunting Pemberian Makanan Tambahan ini tidak hanya diberikan pada anak saja melainkan kepada ibu hamil juga. Program Pemberian Makanan Tambahan perlu disesuaikan dengan kondisi lokal setempat terutama keadaan pangan lokalnya. Tujuan akhir dari program ini ialah untuk memastikan anak-anak mendapatkan gizi yang sesuai agar mereka tumbuh kemang secara optimal dan mengurangi risiko stunting dan masalah gizi lainnya. Mahasiswa peserta pengabdian merancang kegiatan berupa penyuluhan dan pembuatan makanan tambahan. Penyuluhan dilakukan secara langsung dengan metode ceramah mengenai pencegahan stunting yang diawali dengan pre test, pemaparan materi, dan post test. Materi penyuluhan terdiri dari dua materi utama, yakni mengenai ASI dan MPASI yang ditujukan sebagai upaya untuk mencegah stunting. Padai akhir sesi pematerian dibagikan PMT berupa nasi dan nugget ikan yang dapat dipraktikkan di rumah masing-masing oleh ibu hamil dan ibu balita. Kata Kunci: ASI; MPASI; pemberian makanan tambahan